Kajian Penyusunan Laporan Keuangan pada Koperasi Karyawan Mandiri Perum Damri Surabaya - Tarisa Dana Shobiha; Wiratna Wiratna (Jurnal Pengabdian Masyarakat, 2024)
In accordance with Law No. 25 of 1992 Chapter I Article 1 paragraph (1) concerning cooperatives. Cooperatives are business entities whose members are individuals or cooperative legal entities based on cooperative principles as well as people's economic movements based on the principle of family. Cooperatives are formed and managed democratically to meet the needs of members without making profit the main goal because cooperatives are established to improve the economic welfare of their members. The characteristics of cooperatives that distinguish them from other business entities are that cooperative members have a dual identity, namely members as owners and at the same time users of cooperative services. The history of cooperatives initially began in the 20th century. The history of cooperatives began with the results of small businesses that were not spontaneous and carried out by the common people. Low economic capacity encouraged small businesses to escape from suffering. Cooperatives were introduced in Indonesia in 1896 where the establishment of cooperatives was pioneered by R. Aria Wina Atmaja in Purwokerto, Central Java. On July 12, 1947, the cooperative movement in Indonesia held its first cooperative congress in Tasikmalaya. The date of the congress was later determined as Indonesian Cooperative Day. The existence of cooperatives in Indonesia is regulated in the 1945 Constitution article 33 paragraph 1 and Law no. 17 of 2012 concerning cooperatives. In Indonesia there are several types of cooperatives including savings and loan cooperatives, producer cooperatives, multi-purpose cooperatives, consumer cooperatives and many more including employee cooperatives. Employee cooperatives are cooperatives whose members are employees of the company itself without outside communities.